Development of a simulation model of a Company X shunting yard - Aphane, Armstrong Thabiso (My University, 2016)
It was realised that there are inefficiencies at Company X’s plant K shunting yard; service time was long and the idling time of the locomotives was long. Locomotives can be utilised for other purposes in the plant. This has implication in resource planning and productivity in the company. The study deals with the simulation of the Company X rail network in plant K. The focus is on how shunting and product transportation takes place. A background on the study is given, taking into consideration elements which have been included in the study. These include the locomotives and the Block Train Rail Tanker Cars (RTCs). These containers transport different products from Town L to Town M. The study focuses on the transportation of five products. The study also includes the domestic and international Product E trains arriving at the Product E loading and offloading zone. Simulation model which represents the current-state situation was developed, using SIMIO software package. The study examined how service speed during the process of loading and offloading of products in the plant can be improved. The study also focused on locomotives travelling speed and idling time. Conclusions and recommendations have been made on the model developed. The results obtained were also discussed and analysed.
Thesis (M.Com. (Marketing Management and Information Systems))--University of the Witwatersrand, Faculty of Commerce, Law and Management, School of Economic and Business Sciences, 2016.
Keywords: Railroad yards--Mathematical models; Railroads--South Africa--Management; Railroads--Switching